First big book of the ocean - Hughes, Catherine D. (2013)
Introduces several of the ocean's species, provides profiles of creatures, from dolphins and sharks to sea otters and penguins, while sharing facts about their characteristics, diets, and habitats.
Includes index.
Keywords: Ocean -- Juvenile literature; Marine ecology -- Juvenile literature; Ocean; Marine ecology